PENGARUH PENERAPAN STRATEGI ONE TO ONE TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII SMPN 7 LUBUK BASUNG - Sartika, Ira; Rismen, Sefna; Pratiwi, Merina (Pendidikan Matematika, 2014)
ABSTRACTThis research were based on the lack of studentsâ activity and studentsâ understanding of mathematical concept that still low. This research aims to know the studentsâ activities and studentsâ understanding of mathematical conceptÂ  by implementing the One to One strategy in class VIII of SMPN 7 Lubuk Basung. This was an experimental research. The population was studentsâ class VIII of SMPN 7 Lubuk Basung. The experimental class was VIII.I and the control class was VIII.2. The Instrument of the research were observation form for the studentsâ activities and the final tes for the studentsâ understanding of mathematical concept. During the process of teaching by implementing One to One strategy, the studentsâ activities increase. The technique of data analysis was t-test one way and the result is Â = 5,95 and = 1,69. Because >Â it can be concluded that studentsâ understanding of mathematical concept by implementing Â One to One strategy was better than studentsâ understanding of mathematical concept by implementing conventional learning in class VIII of SMPN 7 Lubuk Basung.